Systematic review: the management of hepatic cyst infection. Issue 3 (12th December 2014) - Lantinga, M. A.; Geudens, A.; Gevers, T. J. G.; Drenth, J. P. H.
Summary Background Cyst infection is a severe complication of hepatic cystic disease. However, an evidence‐based treatment strategy is not available. Aim To assess the available treatment strategies and provide a treatment advice for de novo hepatic cyst infection. Methods We systematically searched PubMed (1948–2014), EMBASE (1974–2014), and the Cochrane Library (until 2014) for studies involving humans (≥18 years) treated for a hepatic cyst infection. We extracted data on patient characteristics, treatment and follow‐up. Results We identified 41 articles; all were case series or case reports, implicating a high risk of bias. We included 54 hepatic cyst infection cases (male 39%; mean age 63 ± 12 years; diabetes 6%; dialysis 19%; transplant recipients 30%). Initial therapy consisted of antimicrobial (56%), percutaneous (31%) or surgical treatment (13%). We identified 42 antimicrobial regimens consisting of 23 different combinations. Most used antibiotic classes were quinolones (34%) and cephalosporins (34%). Antimicrobials failed in 70% of cases, eventually requiring percutaneous or surgical treatment in, respectively, 37% and 27%. Recurrent hepatic cyst infection was frequent (20%). Median time to recurrence was 8 weeks (IQR 3–24 weeks). In 46%, recurrence occurred in renal transplant recipients. Cyst infection related deaths occurred in 9%, of whom 40% were on dialysis. Conclusions The literature shows that treatment of hepatic cyst infection is highly heterogeneous. We recommend first line treatment with oral ciprofloxacin. In case of failure, percutaneous cyst drainage needs to be considered.